Taxonomy of haemolytic and/or proteolytic strains of the genus Acinetobacter with the proposal of Acinetobacter courvalinii sp. nov. (genomic species 14 sensu Bouvet & Jeanjean), Acinetobacter dispersus sp. nov. (genomic species 17), Acinetobacter modestus sp. nov., Acinetobacter proteolyticus sp. nov. and Acinetobacter vivianii sp. nov - Nemec, Alexandr; Radolfova-Krizova, Lenka; Maixnerová, Martina; Vrestiakova, Eliska; Jezek, Petr; Sedo, Ondrej (International journal of systematic and evolutionary microbiology, 2016)
We aimed to define the taxonomic status of 40 haemolytic and/or proteolytic strains of the genus Acinetobacter which were previously classified into five putative species termed as genomic species 14BJ (n=9), genomic species 17 (n=9), taxon 18 (n=7), taxon 19 (n=6) and taxon 20 (n=9). The strains were recovered mostly from human clinical specimens or soil and water ecosystems and were highly diverse in geographical origin and time of isolation. Comparative analysis of the rpoB and gyrB gene sequences of all strains, and the whole-genome sequences of selected strains, showed that these putative species formed five respective, well-supported clusters within a distinct clade of the genus Acinetobacter which typically, although not exclusively, encompasses strains with strong haemolytic activity. The whole-genome-based average nucleotide identity (ANIb) values supported the species status of each of these clusters. Moreover, the distinctness and coherence of the clusters were supported by whole-cell profiling based on MALDI-TOF MS. Congruent with these findings were the results of metabolic and physiological testing. We conclude that the five putative taxa represent respective novel species, for which the names Acinetobacter courvalinii sp. nov. (type strain ANC 3623T=CCUG 67960T=CIP 110480T=CCM 8635T), Acinetobacter dispersus sp. nov. (type strain ANC 4105T=CCUG 67961T=CIP 110500T=CCM 8636T), Acinetobacter modestus sp. nov. (type strain NIPH 236T=CCUG 67964T=CIP 110444T=CCM 8639T), Acinetobacter proteolyticus sp. nov. (type strain NIPH 809T=CCUG 67965T=CIP 110482T = CCM 8640T) and Acinetobacter vivianii sp. nov. (type strain NIPH 2168T=CCUG 67967T=CIP 110483T=CCM 8642T) are proposed.
Keywords: Sequence Analysis, DNA; bakteriální geny; techniky typizace bakterií; Phylogeny; DNA, Bacterial; Genes, Bacterial; spektrometrie hmotnostní - ionizace laserem za účasti matrice; sekvenční analýza DNA; fylogeneze; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Acinetobacter; DNA bakterií; Bacterial Typing Techniques